STUDI BANDING PENATAAN RUANG LUAR PADA RUSUN RAWA BEBEK DAN RUSUN CIPINANG MUARA - Putri, Anggie Angellina; Widiyanti (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2021)
The Government's policy to develop housing vertically is regulated in Law number 20 of 2011concerning flats, including their management policies. Flats are the answer to the limited land forsettlements in urban areas. Due to the high price of land in big cities, people are forced to buy housesoutside the city. The arrangement of outer space in flats can be planned in various areas outside thebuilding and various methods that can be applied to flats in order to achieve the desired comfort. TheRawa Bebek Flats are located at the East Flood Canal Inspection, Pulo Gebang Village, CakungDistrict, East Jakarta, and Cipinang Muara Flats, located at Jalan Cipinang Muara 2 No.206 PondokBambu Village, Duren Sawit District, East Jakarta City. The problems in this research are what are thebenefits of outdoor spatial planning and how are the outer space standards in flats. The purpose of thisstudy is to find out how the outer space is arranged in the Rawa Bebek and Cipinang Muara flats andalso to inform readers about how the outdoor layout is implemented. The method to be used in thisresearch is a combination of two methods, namely descriptive and qualitative. Descriptive analysis willbe used on research variables regarding the outer layout of the flats. The results showed that RawaBebek Flats and Cipinang Muara Flats have parking lots, parks, sports fields and places of worship thatfunction properly, and are in accordance with standards.